Modification in the microstructure of sodium carboxymethylcellulose/polyvinyl alcohol polyblend films through the incorporation of NaNO3 for energy storage applications - Vipin Cyriac, Ismayil; Mohd Noor, Ikhwan Syafiq; Rojudi, Z. E.; Sudhakar, Y. N.; Chavan, Chetan; Bhajantri, Rajashekhar F.; Murari, M. S. (John Wiley and Sons, 2022)
In this work, the effect of NaNO3 salt concentration (0, 5, 10, 15, 20, 25, and 30 wt.%) on the structural, electrical, and mechanical properties of Na-carboxymethyl cellulose/polyvinyl alcohol polyblend electrolyte films has been studied. X-ray diffraction showed an increase in the amorphous phase of the polymer blend with increasing salt concentration up to samples containing 20 wt.% of NaNO3 supported by the scanning electron microscope studies. Fourier-transform infrared analysis confirmed the complexation of the salt via coordinate bond/hydrogen bond with –OH and –CH groups of the polymer blend. The (Formula presented.) of the samples have been found to increase with salt concentration indicating transient cross-links. Nyquist plot fitting has been performed to evaluate the transport properties; hence carrier concentration influences ionic conductivity. The sample complexed with 20 wt.% of NaNO3 revealed the highest room temperature conductivity of 1.75 × 10−4 S cm−1, among all other samples with suitable mechanical strength to be incorporated into energy storage devices. The highest conducting electrolyte has been incorporated into a primary battery to showcase its potential application in energy storage devices.